BOUNDED ETHICALITY, BOUNDED RASIONALITY DAN ABSORPTIVE CAPASITY DALAM STRATEGI KOGNITIF MELALUI DESAIN ORGANISASI - Aribowo, Fajar; Nakuloadi, Hening; Indriyanti, Aris; Setiawan, Edi (PRIMA EKONOMIKA, 2024)
ABSTRACT Strategic cognition is seen as a legitimate field for theory building and empirical research in strategic management. Ethical limitations, limited rationality and the absorptive capacity of a leader can influence organizational strategy. The aim of this research is to identify the influence of bounded ethics, bounded rationality and leader absorptive capacity on cognitive strategies in designing organizations. The review analysis used 10 articles that were considered relevant. The results of the analysis show that the success of cognitive strategies is not only based on intelligence or learning absorption capacity, but also on a strong ethical foundation and the ability to make decisions rationally. Effective cognitive strategies require organizations that are able to learn from experience, adopt innovations, and adapt to environmental changes. With ethical limitations, limited rationality and poor absorption capacity will result in poor cognitive strategies which can result in poor organizational structure. Keywords: cognitive strategy, ethical limitations, limited rationality, absorptive capacity, organizational design